THE SPEECH ACT EXPRESSIVE FUNCTIONS WITHIN THE INTERACTIONS OF TOURISM ACTORS WITH THE JAPANESE TOURISTS IN BALI - A.A. Ayu Dian Andriyani (Jurnal Lingua Idea, 2018)
This qualitative research within the tourism domain aims at describing the tourism actors expressive speech act in both formal and informal situations. The main theory used to conduct the analysis is the speech act referring to the tourism actors’ expressive speech act functions in providing services to the tourists, especially those coming from Japan. This research is conducted in Badung and Gianyar, Bali as both locations have the highest numbers of Japanese tourists. The primary data source is written utterances from the tourism actors containing the expressive functions, supported with the secondary data source in the form of documents on the number of tourists in Bali. The data are collected through observation, listening and writing as well as recording and in-depth interview followed with Spradley analytical technique consisting of domain analysis, taxonomy analysis, componential analysis and cultural thematic analysis. Based on the result of analysis, this research shows that the tourism actors when providing services to the Japanese tourists in both formal and informal situations use the expressive functions to express gratitude, compliment, apology, sympathy, and greeting when interacting as the best hospitality forms in their position as the service providers in the tourism domain